Implementing Flipped Learning in Teaching Sociolinguistic Analysis - Ismatovna, Baybabayeva Shoiraxon; Nilufar, Usmanova (Research Parks Publishers, 2023)
The article deals with the issues based on implementing flipped learning in teaching sociolinguistic analysis. The main attention is focused on the selection of the